2008
DOI: 10.1016/j.actbio.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogel mechanical properties and mesh size on vocal fold fibroblast extracellular matrix production and phenotype

Abstract: Current clinical management of vocal fold (VF) scarring produces inconsistent and often suboptimal results. Researchers are investigating a number of alternative treatments for VF lamina propria (LP) scarring, including designer implant materials for functional LP regeneration. In the present study, we investigate the effects of the initial scaffold elastic modulus and mesh size on encapsulated VF fibroblast (VFF) extracellular matrix (ECM) production toward rational scaffold design. Polyethylene glycol diacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
134
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(147 citation statements)
references
References 56 publications
(103 reference statements)
13
134
0
Order By: Relevance
“…20 The hydrogels in the current study were formed with 10% 10 kDa PEGDA, which has been estimated to have a mesh size of 280 Å . 21 Proteins having radii smaller than the hydrogel mesh size enjoy relatively free diffusion through the polymer. 22 Mature BMP-2 is a small protein (*16 kDa), and it has been suggested that it dimerizes immediately after synthesis.…”
Section: Figmentioning
confidence: 99%
“…20 The hydrogels in the current study were formed with 10% 10 kDa PEGDA, which has been estimated to have a mesh size of 280 Å . 21 Proteins having radii smaller than the hydrogel mesh size enjoy relatively free diffusion through the polymer. 22 Mature BMP-2 is a small protein (*16 kDa), and it has been suggested that it dimerizes immediately after synthesis.…”
Section: Figmentioning
confidence: 99%
“…T ECHNIQUES that could precisely pattern hydrogels with tunable geometric shape and size in micro/nano scale are desired for developing hydrogels' applications in drug delivery [1], cell encapsulation [2], [3], cell-environment interaction research [4], [5] and tissue engineering [6]- [8]. To date, three-dimensional micro hydrogel structures have been created by a variety of methods, including photolithography, softlithography (e.g., micro-contact printing, microfluidic patterning, and micro molding) [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Second, hydrogels are optimal in terms of mechanical compatibility with the brain and spinal cord tissue, Young's modulus values are in the range 1,700-2,000 Pa [34]. The compatibility of the mechanical characteristics is determining during the differentiation of progenitor cells [35] and influences overall success of implantation [36]. Third, hydrogels are promising drug compounds in the injury site [37].…”
Section: Long-term Neurological and Behavioral Results Of Biodegradabmentioning
confidence: 99%